A Proposed Algorithm for Image Enhancement using DMWT - Fahdel, Shaimaa A (Al-Nahrain Journal of Science, 2012)
This paper proposes a method of color image enhancement using cascaded application of multiwavelet transform. Our enhancement contains two fields one for remove or decrease the amount of noise from noisy image while the other field deals with applying mean filter for give the resultant image more soft appearance and to make the image more smoother. Also, it suggests a method for computing the multiwavelet transform using the 1st order approximation. The proposed method of the enhancement showed an acceptable result in comparison with the conventional methods that are used for image enhancement. The proposed algorithm and the evaluation test carried using Delphi V.5 package.